Evaluation of the administrative directive management and educational organizational climate of the educational institution N ° 2022 "Sinchi Roca" Ugel 04. Comas - Lima 2018 - Vásquez Zavaleta, Asunciona Edith (2019)
The scientific research we have carried out is basic, non-experimental causal correlation, the study factors are two: administrative management of the Director and the teaching organizational climate at the primary level of the educational institutions of the district of Villa Maria del Triunfo, Lima - 2013. The population is 356 between teachers and administrative staff and the final sample consisted of 40 teachers from the II.EE. I.E.7054, I.E. 7055 "Tupac Amaru II", I.E. 6014, I.E.7073 "Santa Rosa de Lima. I.E.6022 The Immaculate District of Villa María Del Triunfo-Lima ". The design of the research is transeccional, correlacional, causal. bivariate, transversal. For the collection of data, two structured questionnaires were drawn up as a measurement and consist of two aspects: to measure the organizational climate with its dimensions: Communication, confidence, motivation, participation and leadership, which consists of 38 questions. Instead the second is the opinion of the teacher and the administrative, which consists of 14 questions about the management of the Director that was applied to the 40 teachers in the sample. The instruments meet the qualities of validity according to expert juries and reliability. The study proposes the following research hypothesis: the Administrative Management of the director influences the Organizational Climate at the primary level of the educational institutions of the fencing of the district of Villa María del Triunfo, Lima - 2013, according to Spearman's Rho correlation of 0.464 it is MODERATE association of the variables and being highly significant. In addition, according to the tests of independence (*** p <.000) highly significant, the hypothesis is accepted: The administrative management of the director is a factor that significantly influences the organizational climate of the teaching staff at the primary level of educational institutions in the fencing of the district of Villa María del Triunfo, Lima - 2013.